A Methodology for Power Quantities Calculation Applied to an FPGA-Based Smart-Energy Meter - De Oro Arenas, Luis [UNESP] (2021)
A complete description of a field-programmable gate array (FPGA)-based smart energy meter is presented in this article. By implementing the power quantities definitions of the IEEE 1459-2010 Standard, a novel power quality analyzer capable of performing remote monitoring of electric power systems operating under sinusoidal, nonsinusoidal, balanced, and/or unbalanced conditions was developed. In order to ensure portability, the digital signal processing algorithms implemented on the FPGA device were entirely coded in hardware description languages, and all equations of them are fully described to be applied to any digital signal processing environment. These algorithms are completely defined as functions of the grid fundamental frequency, and by adjusting the sampling frequency, the adaptability of all modules developed is ensured. Experimental results were obtained using the developed platform in a three-phase four-wire system operating under several conditions, which were defined by the presence of harmonic components imposed by nonlinear loads and supply voltages, as well as by setting bidirectional power flow in distributed generation scenarios by employing a photovoltaic system. Real-time and parallel processes are validated as well.